RESEARCH OF THE TECHNOLOGICAL MODE OF THE PROCESS OF PORIZATION OF LIQUID GLASS COMPOSITE MATERIALS FOR THERMAL INSULATION IN THE CONDITIONS OF UHF RADIATION - RYMAR, TATYANA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The paper presents the results of research into the technological regime of the process of liquid-glass composition porization under the action of microwave radiation to achieve effective removal of all types of water and obtain heat-insulating materials with high operational properties. It was established that with a radiation power of 500 W in a vacuum environment without rotation of the sample, despite the achieved high temperature value of 110-115 oC, intense swelling was not observed. The decrease in the mass of the sample is due to the mechanism of water removal using a vacuum, which is reduced to a higher mass transfer rate without a vaporization stage. In a vacuum environment, with sample rotation, intense swelling and the formation of a large number of "craters" on the surface of the sample and large through pores in the macrostructure are observed. At atmospheric pressure, there is a sharp drop in temperature at the beginning of the process, which indicates insufficient power of microwave radiation to intensify the swelling process due to significant condensation of moisture on the surface of the sample. With a higher radiation power of 650 W in a vacuum environment, a sharp rise in temperature occurs at the beginning of the process to 90-95 oC, which is due to the beginning of intensive vaporization of free and constitutional water and the creation of a pressure gradient in the sample and its gradual decrease to 55-60 oC, which leads before drying the material. That is, it is impractical to obtain these materials in a vacuum environment, since there are competing processes of water mass transfer and its evaporation. The most optimal conditions for obtaining composite TIMs are the output power of the installation of 650 W and atmospheric pressure. At the very first minute of the process, the temperature rises sharply to 85-90 0C, which slowly increases to 115-120 0C and does not change further. This period is characterized by the most intensive swelling process. The process itself was characterized by ease of adjustment, and the obtained sample has an attractive appearance and a low average density.
Keywords: technological regime; porization process; liquid-glass compositions; microwave radiation; atmospheric pressure; vacuum